PENGARUH KOMUNIKASI, KEAHLIAN KERJA, PENGETAHUAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN MENGGUNAKAN METODE STRUCTURAL EQUATION MODELING - Muhammad Ali Akbar; Rini Sopyani; Hendi Iskandar; Rikzan Bachrul Ulum (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
PT.IMC Tekno Indonesia is a Japanese company engaged in the manufacture of precision plastic components that was established in 1996. Produces supply plastic injection molding components as external products and precision mechanism parts, especially for machine parts. During the year 2019-2020 the performance of the employees of PT. IMC Tekno Indonesia in the office section experienced a decrease in performance, and was not in accordance with the results set by the company in terms of the average aspect of performance appraisal in general. There are various problems in the company that are a concern, namely there are still various employees who are imperfect in doing their jobs, then there is dissatisfaction in their job positions, work skills, and knowledge that not all have broad insight and decreased productivity in completing the desired target. by the company this is due to a lack of discipline in the completion of tasks so that the work is delayed. With the pending work, it can automatically hamper work operations and this results in a decrease in the employee's performance in the eyes of management. This study aims to determine the effect of communication, work skills, knowledge and emotional intelligence on employee performance at PT. IMC Tekno Indonesia. The sampling method used was simple random sampling and the determination of the number of samples in this study using the Arikunto theory resulted in 40 respondents, the data used were primary data with a questionnaire technique, hypothesis testing was carried out with multiple linear regression analysis techniques using a two-tailed test. with the SmartPLS 3.0 2021 application. The results show that Emotional Intelligence has a significant positive effect on employee performance in the office section at PT. IMC Tekno Indonesia while for the variables of communication, work skills and knowledge have no negative and insignificant effect on employee performance.